Marketing research : an Indian perspective - Bajpai, Naval, 1971- (Always learning., 2014)
* The Research in Action feature links the concepts discussed in the chapter to actual industry practice * The case study at the end of each chapter acquaints learners with a variety of organizational scenarios that they may encounter in the future * Numerous examples and problems framed using real data from Indiastat.com and CMIE highlight the business applications of marketing research methods * Marginal definitions reinforce critical concepts and provide simple descriptions for complex theories * Modern statistical software programs explain multivariate statistical techniques using a step-by-step approach.